The effects of in utero bisphenol A exposure on the ovaries in multiple generations of mice - Berger, Amelia (Reprod Toxicol, 2015)
Bisphenol A is used in polycarbonate plastics and epoxy resins. Previous studies show that in utero BPA exposure inhibits germ cell nest breakdown in the F1 generation of mice, but its effects on germ cell nest breakdown and on the ovary in the F2–F3 generations were unknown. Thus, we tested the hypothesis that BPA has transgenerational effects on the ovary. Mice were exposed to BPA in utero (BPA 0.5, 20, or 50 µg/kg/day), and ovaries were collected at postnatal days (PND) 4 and 21 from the F1–F3 generations and subjected to histological evaluation and gene expression analyses. In utero BPA exposure did not have transgenerational effects on germ cell nest breakdown and gene expression on PND 4, but it caused transgenerational changes in expression in multiple genes on PND 21. Collectively, these data indicate that in utero BPA exposure has some transgenerational effects in mice.